The Connachta of Táin Bó Cúailnge - Bulatovas, Romanas (Studia Celtica Posnaniensia, 2017)
Advance in archaeology in the latter half of the 20th century rekindled interest in Táin Bó Cúailnge as a historical source and put the question of real-life identities of its main protagonists back on agenda. Despite the existing orthodoxy that the saga reflects fifth-century warfare between the southern Uí Néill and the Ulaid, some researchers continue questioning the role of the southern Uí Néill as well as the dates assigned to the events of the tale. In this article it is argued that the Connachta of the saga were more likely to be the northern Uí Néill. Furthermore, genealogical link between the two branches of the Uí Néill is put in doubt. Finally, it is suggested that the events of the Táin took place almost 200 years later than commonly believed.